Concurrent speed endurance and resistance training improves performance, running economy, and muscle NHE1 in moderately trained runners - Skovgaard, C.; Christensen, P. M.; Larsen, S.; Andersen, T. R.; Thomassen, M.; Bangsbo, J. (Journal of Applied Physiology, 2015)
The purpose of this study was to examine whether speed endurance training (SET, repeated 30-s sprints) and heavy resistance training (HRT, 80-90% of 1 repetition maximum) performed in succession are compatible and lead to performance improvements in moderately trained endurance runners. For an 8-wk intervention period (INT) 23 male runners [maximum oxygen uptake (VO2max) 59 ± 1 ml/min·kg; values are means ± SE] either maintained their training (CON, n = 11) or performed high-intensity concurrent training (HICT, n = 12) consisting of two weekly sessions of SET followed by HRT and two weekly sessions of aerobic training with an average reduction in running distance of 42%. After 4 wk of HICT, performance was improved (P < 0.05) in a 10-km run (42:30 ± 1:07 vs. 44:11 ± 1:08 min:s) with no further improvement during the last 4 wk. Performance in a 1,500-m run (5:10 ± 0:05 vs. 5:27 ± 0:08 min:s) and in the Yo-Yo IR2 test (706 ± 97 vs. 491 ± 65 m) improved (P < 0.001) only following 8 wk of INT. In HICT, running economy (189 ± 4 vs. 195 ± 4 ml·kg-1·km-1), muscle content of NHE1 (35%) and dynamic muscle strength was augmented (P < 0.01) after compared with before INT, whereas V?o2max, muscle morphology, capillarization, content of muscle Na+/K+ pump subunits, and MCT4 were unaltered. No changes were observed in CON. The present study demonstrates that SET and HRT, when performed in succession, lead to improvements in both short- and long-term running performance together with improved running economy as well as increased dynamic muscle strength and capacity for muscular H+ transport in moderately trained endurance runners.